Enhanced PM2.5 Decreases and O3 Increases in China During COVID‐19 Lockdown by Aerosol‐Radiation Feedback - Jia Zhu; Lei Chen; Hong Liao; Hao Yang; Yang Yang; Xu Yue (Geophysical Research Letters)
Abstract We apply an online‐coupled meteorology‐chemistry model (WRF‐Chem) embedded with an improved process analysis to examine aerosol‐radiation feedback (ARF) impacts on effectiveness of emission control due to Coronavirus Disease 2019 (COVID‐19) lockdown over North China Plain. Emission reduction alone induces PM2.5 decrease by 16.3 μg m−3 and O3 increase by 10.2 ppbv during COVID‐19 lockdown. The ARF enhances PM2.5 decrease by 2.7 μg m−3 (16.6%) and O3 increase by 0.8 ppbv (7.8%). The ARF‐induced enhancement of PM2.5 decline is mostly attributed to aerosol chemistry process, while enhancement of O3 rise is ascribed to physical advection and vertical mixing processes. A set of sensitivity experiments with emission reductions in different degrees indicate that the ARF‐induced enhancements of PM2.5 declines (O3 rises) follow a robust linear relationship with the emission‐reduction‐induced PM2.5 decreases. The fitted relationship has an important implication for assessing the effectiveness of emission abatement at any extent.